2019
DOI: 10.12775/jehs.2019.09.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Features of immune status in different states of uric acid metabolism in female rats

Abstract: zukow@umk.pl 4 OO Bohomolets' Institute of Physiology, Kyїv i.popovych@biph.kiev.ua AbstractBackground. Previously, we found a wide range of uric acid metabolism parameters and functional relationships of uricemia and uricosuria with the parameters of immunity in healthy female rats analyzed. It was found by canonical correlation analysis that both parameters of uric acid metabolism determine the immunity status of rats by 71%. The purpose of this study is to determine the features of immune status in rats wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…The study of the effect of end products of protein and nucleic acid metabolism on the immune system is of interest not only theoretical but also practical in line with the problems of urotoxins and hemodialysis. In previous studies, we found significant links between uricemia and uricosuria, on the one hand, and immune parameters, on the other hand, in both healthy rats [17,18] and patients in Truskavets' spa [19,20,37]. In this experimental study, the spectrum of nitrogenous metabolites was expanded due to creatinine, urea and bilirubin.…”
Section: Introductionsupporting
confidence: 51%
“…The study of the effect of end products of protein and nucleic acid metabolism on the immune system is of interest not only theoretical but also practical in line with the problems of urotoxins and hemodialysis. In previous studies, we found significant links between uricemia and uricosuria, on the one hand, and immune parameters, on the other hand, in both healthy rats [17,18] and patients in Truskavets' spa [19,20,37]. In this experimental study, the spectrum of nitrogenous metabolites was expanded due to creatinine, urea and bilirubin.…”
Section: Introductionsupporting
confidence: 51%
“…Previously, continuing experimental studies [6][7][8]10], by screening correlation links between uricemia and uricosuria, on the one hand, and immunity and microbiota parameters, on the other, registered in each of 44 patients with chronic pyelonephritis and cholecystitis in remission twice (before and after ten days of balneotherapy), we found that raw uricemia determines by 28% nine parameters of immunity as well as bacteriuria and content in E. coli feces. Uricemia, normalized by sex and age, determines by 25% another constellation of immunity parameters as well as content in E. coli feces with impaired enzymatic activity and Klebsiela&Proteus.…”
Section: Introductionmentioning
confidence: 90%
“…In the above experiment in rats [8][9][10], we found that Uric acid level correlated positively with the content in the thymus of Lymphocytes and Macrophages, but negatively correlated with the content of Epitheliocytes, Reticulocytes and Hassal's corpuscles. If these data are transferred to humans, it can be suggested that Uric acid stimulates the differentiation of thymocytes to CD8 + T-cells, instead reducing the formation of CD4 + T-cells.…”
Section: Table 6 Factor Structure Of Canonical Correlation Between Pmentioning
confidence: 96%
“…Previously, we found a wide range of uric acid exchange parameters grouped into four clusters [7] and functional relationships of uricemia and uricosuria with the parameters of immunity in healthy rats analyzed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%